All our activities leave a digital printfoot - Niewdana, Agnieszka; Simiński, Roman (No Limits, 2021)
Every day we take pictures, have conversations via various communicators, send documents, or pay for purchases with a money card. We do not give any consideration to the issue where this data is collected and how it can be used. In the meantime, Internet transactions, online shopping, or even web browsing leave a permanently recorded digital footprint of our online presence. Notwithstanding the fact whether digital footprint identifies us or we remain anonymous, it contains information about our activity that can be used – legitimately or illegitimately.